Cytotoxic iridal-type triterpenoids from Iris tectorum. Issue 34 (26th August 2015) - Zhang, Chun-Lei; Wang, Yan; Liu, Yan-Fei; Liang, Dong; Hao, Zhi-You; Luo, Huan; Zhang, Qing-Jian; Shi, Guo-Ru; Chen, Ruo-Yun; Cao, Zheng-Yu; Yu, De-Quan
Abstract: Seven new iridals (1 –7 ), designated as iritectols C–F, 22-epiiritectol D, 22-epiiritectol E, 22-epiiritectol F together with three known analogues were isolated from the rhizomes of Iris tectorum . Among them, compounds2 and3, 4 and5, and6 and7 were found to be three pairs of C-22 epimers, some of which were separated by chiral column chromatography. This is the first report on the occurrence of epimers of monocyclic iridals. Their structures were elucidated on the basis of extensive spectroscopic analysis. The isolates were evaluated for their cytotoxic activities against five human tumor cell lines. Compound1 but not others exhibited moderate cytotoxic activities, with IC50 values ranging from 4.1 to 9.8 μM. The structure–activity relationship of the tested compounds was briefly discussed. Graphical abstract: